2012
DOI: 10.1590/s0102-33062012000100015
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização florística e estrutural das florestas naturalmente fragmentadas no Parque Estadual do Guartelá, município de Tibagi, estado do Paraná

Abstract: ABSTRACT(Structural and fl oral characterization of the naturally fragmented forests in the Parque Estadual do Guartelá, Tibagy municipality, Paraná, Brazil) Th e Araucaria forest in the region of Campos Gerais in Paraná is naturally fragmented, and is found in patches (capões) or along watercourses. Th e goal of this study was to characterize the structure of these fragments and to evaluate correlations between species distribution and soil variables in Parque Estadual do Guartelá, in the Tibagy municipality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
0
7
0
7
Order By: Relevance
“…Na análise das subparcelas (estrato inferior), apenas os indivíduos de Periandra mediterranea representaram 41 % do total amostrado, sendo a espécie dominante neste estrato (Tabela 1). Esta alta densidade também foi encontrada nos campos com afloramentos rochosos presentes no PEG (CARMO, 2006), mostrando que a adaptação desta espécie aos fatores ambientais locais associados ao seu sucesso reprodutivo, está favorecendo a propagação de suas populações.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Na análise das subparcelas (estrato inferior), apenas os indivíduos de Periandra mediterranea representaram 41 % do total amostrado, sendo a espécie dominante neste estrato (Tabela 1). Esta alta densidade também foi encontrada nos campos com afloramentos rochosos presentes no PEG (CARMO, 2006), mostrando que a adaptação desta espécie aos fatores ambientais locais associados ao seu sucesso reprodutivo, está favorecendo a propagação de suas populações.…”
Section: Resultsunclassified
“…Além disso, Hueck (1972) postulou que áreas marginais de cerrados, em virtude do clima, estariam sendo substituídas pela vegetação vizinha, permanecendo como ilhas dentro de um novo tipo de vegetação. Isto foi observado neste estudo, pois espécies abundantes encontradas nas áreas de cerrado, como Myrsine umbellata, Pera glabrata, Calyptranthes concinna, Copaifera langsdorffii, Casearia sylvestris e Alchornea triplinervia, são também as de maior densidade nas florestas dentro do parque (CARMO, 2006), o que confirma que pequenos relictos, como da área de estudo, são testemunhos da redução dos cerrados em consequência do avanço das florestas pelas condições climáticas atuais (MAACK, 1981).…”
Section: Resultsunclassified
“…Most of the area is covered by grassland physiognomies, with patches of Mixed ombrophilous forest and Cerrado (Veloso et al, 1991). According to Köppen's classification system, the regional climate is Cfb (humid temperate) with direct influence of Cfa (humid subtropical) (Carmo & Assis, 2012).…”
Section: Study Sitementioning
confidence: 99%
“…Despite that, a study by Carmo & Assis (2012) found that forest fragments within the park have a high number of plant species, and a survey of vascular plants deposited in the herbarium of the State University of Londrina found 667 specimens collected between 1987 and 2005, belonging to 61 subfamilies and 243 plant species (Rossetto et al, 2012). In addition, a survey identified 160 species of ferns and lycophytes in PEG, belonging to 54 genera and 19 families (Michelon & Labiak, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tem uma área total de 798,97 hectares e as amplitudes altimétricas podem superar os 450 metros (MELO, 2011), região em que o rio Iapó escavou um cânion com paredes abruptas em rochas da Formação Furnas. Possui também uma elevada riqueza florística, consequên-cia das diversas formas fisionômicas (CARMO, 2006), o que também contribui como um atrativo de natureza ecoturística.…”
Section: Resultsunclassified